(untitled) (Journal of Science Foundation, 2013)
The aim of the study to find out the ratio of raise of serum total protein and serum albumin during amino acid supplementation in burn patients. This interventional study cross sectional study was done in the Department of Biochemistry, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during January 2008 to December 2008. A total of 40 acute burn injury (within 24 hours of burn) patients of 20-45 years age with 15%-30% burn were selected for this study as case. The study subjects were divided into two groups: Group I represent superficial burn & Group II represents deep burn. In group-I, serum albumin was decreased by 19.24% after infusion and in group-II, that was decreased by 22.45% (p<0.05). Serum total protein significantly increased after infusion of amino acid but serum albumin significantly decreased after infusion of amino acid. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14653 J. Sci. Foundation, 9(1&2): 109-113, June-December 2011